Transformations and Availability of Iron to Wheat as Influenced by Phosphorus and Manganese Fertilization in a Typic Haplustept Soil. Issue 9 (15th May 2019) - Dhaliwal, S.S.; Mandal, Agniva
ABSTRACT: An investigation was conducted using Typic Haplustept, sandy loam soil, to investigate the interactive effects of phosphorus (P) and manganese (Mn) fertilization on native iron (Fe) pools in soil and their availability to wheat (cv. PBW-343) crop. Phosphorus fertilization moved Fe from residual mineral fraction of Fe to manganese oxides (MnOX), organic matter (OM), amorphous (AMPOX), and crystalline (CRYOX) Fe and Al oxide fractions. However, Mn application decreased specifically adsorbed (SAD)–Fe and CRYOX–Fe but increased OM–Fe and mineral fraction of Fe. Available Fe in soil decreased as Olsen P and P:Mn ratio increased in the soil. Higher Olsen P (>60 mg P kg −1 soil) reduced mean Fe uptake by shoot. P content and P:Mn ratio in soil as well as in root and shoot were inversely related to Fe concentration in both the plant parts. The role of soil Fe associated with oxides and organic matter was found most notable in Fe nutrition of wheat.